Access to legal abortion by rape victims as a reproductive health right : case study Swaziland and Ethiopia - Aneme, Girmachew (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Dr. Girmachew Alemu Aneme, Faculty of Law, University of Addis Ababa, Ethiopia.